تفسیر تفہیم القرآن: عصرِ حاضر کے فکری و عملی تقاضوں کے تناظر میں افکارِ مودودی کا تحقیقی و تجزیاتی مطالعہ: Tafheem al-Qur’ān: A Critical and Analytical Study of Maududi’s Thought in the Context of Contemporary Intellectual and Practical Demands (Al-Aasar, 2025)
It is a fact that with the passage of time, people's thoughts, customs, society, affairs and even values ​​change. The same thing happens with languages ​​and dialects. With time, language and styles of expression change. Many new colors are also created in the words, meanings, idioms, dialects and concepts of everyday speech. Some of the essential requirements of the modern era change even the ideas and beliefs established for centuries. The interpretations of the Urdu language met the needs of their time to some extent. None of these interpretations could meet the requirements of the present era. The language of some was difficult, while some lacked continuity and fluency. In the context of these aforementioned interpretations, Syedabu'l-Ala Maududi also had the idea in his mind that these interpretations were no longer keeping up with the changing times. He felt the need for a well-reasoned, comprehensive, and simply written commentary that met the demands of the modern age and that, while rejecting Western ideas, concepts, and philosophical explanations, presented the concept of Islam as a comprehensive system of life.